International financial aid - Friedmann, Wolfgang; Kalmanoff, George; Meagher, Robert F. (New York : Columbia University Press, 1966)
This book is the outcome of a research project by the Columbia University School of Law during 1961-5. It starts with a general survey of aid giving covering the total amounts and types of aid and the methods and policies adopted by the aid-giving countries and institutions. This is followed by case studies of some of the aid-receiving countries which form the most interesting sections of the book. These include: the World Bank Loan to the National Railways of Colombia and the Balance of Payments Loan to Colombia during 1954-62 from various sources etc.
Includes index.
Includes bibliographical references (p. [473]-481)
usc 09/08/18
Loans
Keywords: Economic assistance; International finance